2014
DOI: 10.4184/asj.2014.8.6.804
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Distal Fusion Level in the Management of Thoracolumbar and Lumbar Adolescent Idiopathic Scoliosis Using Pedicle Screw Instrumentation

Abstract: Study DesignA retrospective study.PurposeTo determine the exact distal fusion level in the management of thoracolumbar/lumbar adolescent idiopathic scoliosis (TL/L AIS) using pedicle screw instrumentation (PSI).Overview of LiteratureThe selection of distal fusion level remains controversial in TL/L AIS.MethodsRadiographic parameters of 66 TL/L AIS patients were analyzed. The patients were grouped according to the distal fusion level; L3 group (fusion to L3, n=58) and L4 group (fusion to L4, n=8). The L3 group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Moreover, LIV selection in regard to SV and LTV However, longer follow-up might be necessary to observe occurrence of disc degeneration below fusion [32,33]. Moreover, neither selective nor hyperselective fusions significantly affected postoperative LL, which is in accordance with previous literature [14]. However, five patients from the selective group had lumbar hypolordosis at follow-up (although these normative values were obtained from adult patients).…”
Section: Radiological Outcomessupporting
confidence: 83%
See 1 more Smart Citation
“…Moreover, LIV selection in regard to SV and LTV However, longer follow-up might be necessary to observe occurrence of disc degeneration below fusion [32,33]. Moreover, neither selective nor hyperselective fusions significantly affected postoperative LL, which is in accordance with previous literature [14]. However, five patients from the selective group had lumbar hypolordosis at follow-up (although these normative values were obtained from adult patients).…”
Section: Radiological Outcomessupporting
confidence: 83%
“…Recently, some surgeons have tended to reduce their fusion length in posterior procedures as well (hyperselective fusion), using the criteria initially described for anterior surgery, because they strongly believed in the 3D correction potential of pedicle screws and were concerned about the future risk of adjacent degeneration [10,14]. The aim of this study was, therefore, to compare the clinical and radiological outcomes of selective and hyperselective fusions in Lenke 5 AIS operated via posterior approach.…”
Section: Introductionmentioning
confidence: 99%
“…With the use of pedicle screws, the planning for the level of fusion was begun to be performed using flexibility radiographs such as supine bending or fulcrum bending [ 2 , 3 , 7 , 8 , 22 - 24 ]. According to the use of bending radiographs in fusion site selection, the fusion should be ended over the neutralized disc gap in the distal on bending radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Selection of the L3 or L4 vertebra as the LIV in thoracolumbar/lumbar curvatures has been a matter of research in several studies. Kim et al reported successful results with ending the fusion at the L3 level in patients where the midsacral line passes through the L3 vertebra on concave bending radiographs and the rotation falls below Nash and Moe Grade 2 on convex bending radiographs [ 8 ]. Wang et al specified a translation of less than 28 mm and a tilt of less than 25 degrees as the general criteria for LIV selection in patients with Lenke Type 5C scoliosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation